Impact of Flame Thickening on the Predicted Shape and Dynamics of a Turbulent Premixed Flame - Thomas, Cillian; Stuart, Charles; Spence, Stephen (My University, 2025)
This study investigates the impact of flame thickening on the predicted flame shape and transfer function of a premixed methane–air turbulent flame using Large Eddy Simulations (LES). Simple 1D flames were used to identify the general impact of thickening on premixed methane-air flames, followed by a 3D LES study to demonstrate the implications of these effects. The flame was shown to increase in length, with a more broad distribution of heat release rate, as thickening factor increased due to changes in flame consumption speed and its response to strain. The Flame Transfer Function (FTF) was computed for each case, and the differences are discussed. It is shown clearly that the thickening factor F can suppress the appearance of vortex shedding modes by increasing the cut-off frequency of the flame. It has also been shown that decreasing thickening factor can cause the appearance of peaks in the FTF which are not observed experimentally. In this study, large thickening factors were shown to cause the flame to leave the combustor domain and lack the ability to conserve energy. This paper highlights clearly the impact of thickening factor on the flame transfer function and the impulse response.
Symposium on Thermoacoustics in Combustion: Industry meets Academia (SoTiC 2025)
PUBLISHED
Trondheim, Norway
Keywords: Flame Transfer Function; Large Eddy Simulation; Artificially Thickened Flame; Premixed Flame